Androgen receptor polymorphism, mental rotation, and spatial visualization in men. (July 2021) - Sankar, Janani S.; Hampson, Elizabeth
Abstract: Circulating levels of testosterone (T) have been hypothesized to influence spatial cognition in adult men, but empirical support for this idea is mixed. Many of testosterone's effects are mediated by the classic nuclear androgen receptor (AR), which contains a polymorphic glutamine repeat (CAG repeat sequence) that varies significantly across individual men and confers differences in receptor function and therefore individual responsivity to T. We genotyped the AR CAG repeat length in 146 healthy adult men who also performed cognitive tests of mental rotation and spatial visualization. Circulating T concentrations were measured in saliva. CAG repeat length was found to be a significant predictor of spatial scores on tests of visualization but not mental rotation. A weaker AR was associated with lower visualization scores. In contrast, T itself, but not CAG repeat length predicted scores on two mental rotation tests. These results support the view that T action in the brain modestly influences spatial cognition in healthy men, but suggest that T's effects on mental rotation might not be AR-dependent and instead occur through an alternative mechanism. Highlights: Polyglutamine (CAG) repeat genotyped in androgen receptor gene of healthy adult men. Standardized cognitive tests used to measure 2 distinct forms of spatial cognition. Testosterone quantified from saliva collected concurrently with task performance. CAG repeat length predicted spatial visualization but not mental rotation test scores. Salivary testosterone correlated inversely with mental rotation task performance.